Supplementation of cockle shells-derived calcium for maintaning serum calcium level in pregnant and lactating jamnapari and boer goats - Mohd Yusoff, Husna Fasihah (2016)
The optimum nutrition, minerals and better care of pregnant and lactating does are very important. One of the most important mineral in the diet is calcium. Calcium supplements used in this study come from cockle (Anadara granosa) shells. This is because shells are very similar to bones and in form of CaCO3 that can provide the strong basis for the calcium potential source. Blood and feed samples were taken to evaluate the level of calcium in diet and serum calcium level in goats, respectively. The observation in this study was first looking at the feed analysis and followed by calcium serum concentration analysis. Feed analysis was used to analyze the calcium content in feed provided by the farmer. Then the research proceeds with blood analysis. Samples were collected before and after supplementation of calcium in order to identify the calcium level in goat’s blood. A total of 45 goats were chosen in this study. Calcium is an essential mineral to have in the diet as it builds strong bones and sometimes we may not be aware of. Deficiency of calcium can cause reproductive problems. This is because calcium is very important for smooth muscle function. This study is very important to highlight the influence of pregnancy and lactation on the calcium concentration in goats’ blood serum. Most of the feed given by the farmer contain less calcium level compared to the calcium level suggested by the previous from other other researchers. Thus, it is important for the goats to consume enough calcium in order to maintain adequate blood and bone calcium levels. Independent t-test was used to compare serum calcium concentration in mmol/L. Result were expressed as mean ± standard error mean (SEM). A probability of p<0.05 was considered significant for the statistical test. There was a statistically significant difference between groups as determined by t-test for post-delivery stage. A test revealed that the changes between with and without supplementation were statistically significantly at p < 0.05, whereas, significant difference occurred between mid-trimester and late-gestation stages in Jamnapari goats. However from overall results from the tables shows no significant different happened among all other stages. Finally, it seems that most of the feed types were shown a lower calcium level compared with the calcium level suggested by the other researches. As the feeds contain low concentrations of calcium, it is important to supplement the does with calcium. In this study calcium source was obtained from cockle shells. Besides that, the declining and rising of serum calcium level shown in supplemented group, contrarily it was not happening to the non-supplemented group. It seems that, the serum calcium level during pregnancy and lactating stage is really unpredictable. This situation happened might be due to several factors such as hormonal concentration (progesterone and estrogen level) along gestation and lactation period, fetus development, nutrition, excretion through waste (feces, urine and sweat) and skeletal formation and mineralization process. On the other hand, there was no significant different happened between two different breeds in calcium serum level during gestation and post-delivery. Finally, through this research and from overall observation, animal with calcium supplement maintain the normal calcium level in the body within the range and the level keep on increase appropriately for both breeds.